1994
DOI: 10.1177/001440299406000407
|View full text |Cite
|
Sign up to set email alerts
|

Parents of Students with Disabilities and Open Enrollment: Characteristics and Reasons for Transfer

Abstract: This study examines the characteristics of students with disabilities who participate in Open Enrollment (one of seven enrollment options available in Minnesota), the reasons they participate, and the sources of information and decision-making process involved with choosing another district. Surveys of 347 parents revealed three primary reasons for transferring their children: The child's special education needs being better met at the new district, more personal attention from the teacher, and dissatisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Bagley and Woods (1998) suggested that parents were acting pragmatically to choose a school that represented a best fit for their child's needs. Another suggestion in the literature is that part of this pragmatic decision‐making may be based on the experience that parents feel their child has had of inclusion in their primary school; if this has not been positive then they may be more likely to opt for special school provision at secondary age (Bagley et al., 2001; Jenkinson, 1998; Whitaker, 2007; Ysseldyke, Lange and Gorney, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bagley and Woods (1998) suggested that parents were acting pragmatically to choose a school that represented a best fit for their child's needs. Another suggestion in the literature is that part of this pragmatic decision‐making may be based on the experience that parents feel their child has had of inclusion in their primary school; if this has not been positive then they may be more likely to opt for special school provision at secondary age (Bagley et al., 2001; Jenkinson, 1998; Whitaker, 2007; Ysseldyke, Lange and Gorney, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…However, of the 193 parents surveyed, 52 per cent reported that their child attended a mainstream school and of this group, '72 per cent would continue to prefer the mainstream setting ' (p. 193), and as pointed out earlier in relation to the study by Male (1998), it is possible that perceptions may now be different because mainstream schools have had more time to develop their skills and knowledge. A survey of 141 parents of children transferring schools in the state of Minnesota by Ysseldyke et al (1994) found that 40 per cent of the parents were dissatisfied with the child's former school. The authors also gave a breakdown of the figures according to the disability identified by respondents on the survey questionnaire; a higher figure of 50 per cent dissatisfaction is reported by parents of children with emotional behavioural disorder, learning disability, mental retardation and multiple disabilities.…”
Section: School Variables Experience Of Inclusion During the Primary mentioning
confidence: 99%
“…For example, while there were no charter schools in Minnesota in 1991, more than half of the charter schools that have emerged since then are located within these two districts 3. According to Ysseldyke et al[30], only about five percent of 1990-1991 open enrollment transfer students were students with disabilities. This percentage is relatively low; during the same year, roughly 11% of all Minnesota public students were classified as special education students.…”
mentioning
confidence: 99%
“…The literature on school choice for parents of students with disabilities demonstrate a diversity of motivations. In a recent review of the literature on the factors influencing parents of students with disabilities, Mawene and Bal (2018) demonstrated that school choice is influenced by school-based factors such as the availability of special education resources including special education programmes (Ysseldyke, Lange, and Gorney 1994;Bryne, 2013), facilities and specialist staff (Bajwa-Patel and Devecchi 2014) smaller class size (Jenkinson 1998), positive attitudes among teachers (Glenn-Applegate et al 2016), communications between parents and teachers and individual attention to their children (Finn et al, 2006). Furthermore, family-based factors such as shorter distance to school (Jessen, 2003), social continuity such as siblings support (Ysseldyke et al1993;Jessen, 2003) and family beliefs about disability could influence choices towards inclusive schools or segregated settings (Runswick-Cole, 2008).…”
Section: Theory and Research Review On Parental School Choicementioning
confidence: 99%